BF175 inhibits endometrial carcinoma through SREBP-regulated metabolic pathways in vitro. (1st March 2021) - Wang, Qiong; Hu, Ruofan; Li, Weihua; Tai, Yanhong; Gu, Weiting; Das, Bhaskar C.; Yang, Fajun; Ji, Junyuan; Wang, Chenguang; Zhou, Jie
Abstract: Elevated lipogenesis is an important metabolic hallmark of rapidly proliferating tumor such as endometrial carcinoma (EC). The sterol regulatory element-binding protein 1 (SREBP1) is a master regulator of lipogenesis and involved in EC proliferation. BF175 is a novel chemical inhibitor of SREBP pathway, and has shown potent anti-lipogenic effects. However, the effect of BF175 on EC cells are yet to be determined. In the present study, we found that BF175 decreased cell viability, colony formation and migratory capacity, inducing autophagy and mitochondrial related apoptosis in EC cell line AN3CA. Z-VAD-FMK partially attenuated the effect of BF175 on AN3CA. In addition, BF175 significantly downregulated SREBPs and their downstream genes. The levels of free fatty acids and total cholesterol were also inhibited. Microarray analysis suggested BF175 treatment obviously affected lipid metabolic pathways in EC. Taken together, we validated BF175 exhibited anti-tumor activity by targeting SREBP-dependent lipogenesis and inducing apoptosis which mitochondrial pathway involved in, suggesting that it's potential as a novel therapeutic reagent for EC. Highlights: BF175 inhibited cell growth and migration in endometrial carcinoma (EC) cells. Autophagy and mitochondrial related apoptosis in EC cells were induced by BF175. Z-VAD-FMK partially attenuated the effect of BF175 on EC cells. BF175 exhibited anti-tumor activity through targeting SREBP related lipogenesis.